Unveiling The Impact of Technological Advancements on Macroeconomic Stability and Labor Market Dynamics - Herman Oddyansyah Felani; Nirdukita Ratnawati (Syntax Corporation, 2023)
The rapid development of information and communication technology has an impact on economic growth that is increasingly varied. Economic stability is a basic prerequisite for achieving improvements in people's welfare through high growth and improved growth quality. In line with that, technological progress also has a significant impact on the dynamics of the labor market. The labor market has a mutual relationship between companies and labor. If developing countries want to achieve higher economic development, they must increase trade and physical capital with a stable macroeconomic environment. But on the other hand, technology automatically leads to a decrease in employment and wages. This changes the relative demand for jobs.